2015
DOI: 10.4103/0975-5950.183852
|View full text |Cite
|
Sign up to set email alerts
|

Retromandibular approach in the management of condylar fractures by open reduction and internal fixation a prospective study

Abstract: Aim:To evaluate the efficacy and safety of the retromandibular approach in the management of condylar fractures by open reduction and internal fixation (ORIF).Materials and Methods:A total of 20 patients with unilateral mandibular condylar fractures underwent ORIF using retromandibular approach. Pertinent data were collected and subjected to evaluation.Results:The retromandibular approach was found to be expeditious in adequately exposing the fracture site and enabling ORIF. The anatomic reduction of the fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…The small incision size and the height (higher level) of the intra-articular condylar head fracture make it a difficult task to reach and reduce the segments. The main reason for considering this approach as one of the choices in the management of diacapitular fractures is the lower risk of facial nerve injury as well as the most conservative of the condylar approaches in the context of soft tissue handling [ 16 ]. In the modified retromandibular approach, the area in the middle of the buccal and marginal mandibular branch of the facial nerve is utilized for dissection, thereby ensuring the protection of the facial nerve and preventing additional morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…The small incision size and the height (higher level) of the intra-articular condylar head fracture make it a difficult task to reach and reduce the segments. The main reason for considering this approach as one of the choices in the management of diacapitular fractures is the lower risk of facial nerve injury as well as the most conservative of the condylar approaches in the context of soft tissue handling [ 16 ]. In the modified retromandibular approach, the area in the middle of the buccal and marginal mandibular branch of the facial nerve is utilized for dissection, thereby ensuring the protection of the facial nerve and preventing additional morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Salivary fistula is a potential complication which can be prevented by watertight closure of the parotid capsule. 23 In our study, in 2 cases salivary fistula was observed which was treated by antisialagogues (Tab. Glycopyrrolate 1 mg, BD) for 7 days.…”
Section: Stability Of Fractured Fragment and Osteosynthesis Devicementioning
confidence: 58%
“…[ 28 ] Other benefits include good cosmesis and adequate exposure for manipulation and reduction of the fracture and for placement of fixation in condylar neck and subcondylar fractures. [ 29 30 ] Retromandibular approach is an effective and safe technique, especially for displaced subcondylar fractures. [ 31 ]…”
Section: Discussionmentioning
confidence: 99%